Zero Tolerance vs Restorative Justice in the United States - Kimberly Battjes; Lilly Zane Kaplan (Center for Educational Policy Studies Journal)
As schools across the United States begin to move away from the harsh Zero Tolerance policies that characterised the better part of the previous three decades, there is an opportunity to change the focus of school discipline. Frequently, school discipline policies are centred on punitive approaches that separate students from their peers. Rather than meeting the needs of these students, schools alienate them from their peers, teachers, and school communities. The goal of the education system is to provide children and adolescents with a quality education that will allow them to grow into productive and participating members of society. Zero Tolerance and school discipline policies were created to protect students, but, in practice, these policies have proven to be harmful and have unintended consequences. Too often, punitive disciplinary action in the school setting puts students on a pathway that leads into the juvenile or criminal justice system. Although the Zero Tolerance policy is a federal initiative, many states are beginning to realise the harmful impacts this policy has on students, especially marginalised students. As a result, states are beginning to pass legislation that veers away from Zero Tolerance, focusing more on alternatives like restorative practices. This article will explore these issues and share information on policies current states are using and the implications of these policies on students, as well as the school-to-prison pipeline.